Use of OPC to improve setting and early strength properties of low calcium fly ash geopolymer concrete cured at room temperature - Nath, Pradip; Sarker, Prabir (Elsevier BV, 2015)
Most previous works on fly ash based geopolymer concrete focused on concretes subjected to heat curing. Development of geopolymer concrete that can set and harden at normal temperature will widen its application beyond precast concrete. This paper has focused on a study of fly ash based geopolymer concrete suitable for ambient curing condition. A small proportion of ordinary Portland cement (OPC) was added with low calcium fly ash to accelerate the curing of geopolymer concrete instead of using elevated heat. Samples were cured in room environment (about 23oC and RH 65±10%) until tested. Inclusion of OPC as little as 5% of total binder reduced the setting time to acceptable ranges and caused slight decrease of workability. The early-age compressive strength improved significantly with higher strength at the age of 28 days. Geopolymer microstructure showed considerable portion of calcium-rich aluminosilicate gel resulting from the addition of OPC.